A lower leg surrogate study to investigate the effect of quadriceps–hamstrings activation ratio on ACL tensile force. Issue 9 (September 2022) - Hermann, Aljoscha; Jung, Alexander; Gruen, Alexandra; Brucker, Peter U.; Senner, Veit
Abstract: Objectives: Many studies have investigated the relationship between muscle activation and tensile force of the anterior cruciate ligament. These studies lacked a holistic representation of the muscle status. For instance, they were limited with respect to the peak muscle forces, number of muscles, and possible muscle activation patterns. Design: This study used a knee surrogate including ten muscles with motor-controlled muscle force activation crossing the knee joint, thus providing a fully muscle-supported knee joint. Methods: Anterior cruciate ligament tensile force is measured in different knee flexion and extension movements to evaluate ratios of quadriceps/hamstring muscle activations in low hip angle setups. Results: Increasing the extension of the leg increased anterior cruciate ligament tension forces. Different quadriceps/hamstring ratios had different effects on anterior cruciate ligament tension forces during unrestricted flexion and extension movements. This was dependent on the direction of movement. Sole hamstring activation increased the anterior cruciate ligament tensile forces in extension movements compared with flexion movements. Sole quadriceps activation provoked greater anterior cruciate ligament tensile forces in flexion than in extension. This was not prominent in the test in which the other muscle groups counteracted the dominant muscle group. Conclusions: The findings from the present study demonstrate that active hamstring activation can reduce the load on the anterior cruciate ligament, and the dominant quadriceps increase anterior cruciate ligament loads for knee flexions of less than 40°. Moreover, the anterior cruciate ligament is loaded differently in flexion or extension movements with flexion movements, resulting in higher anterior cruciate ligament loads.